Factors affecting survival prognosis of patients with rectal cancer after neoadjuvant chemoradiotherapy - Li, Baokun; Han, Jiachao; Wang, Feifei; Yu, Bin; Wang, Guiying; Yang, Fei (Frontiers in Oncology, 2025)
ObjectiveTo identify potential factors influencing the survival prognosis of locally advanced rectal cancer patients receiving neoadjuvant chemoradiotherapy.MethodsA retrospective study was conducted to collect data from January 2009 to December 2020 on 270 patients with locally advanced rectal cancer who were admitted to the Fourth Hospital of Hebei Medical University. The clinical data of patients before and after neoadjuvant chemoradiotherapy and postoperative treatment were compiled. The endpoints of the study were disease-free survival and overall survival of the patients. The univariate and multivariable regression analysis were used to identify factors that influence the patients’ survival prognosis.ResultsUnivariate analysis showed that factors associated with good prognosis in neoadjuvant chemotherapy patients included age <65 years, CEA value ≤5ng/mL, lymphocyte count >1.5×109/L, normal albumin level, NLR ≤2.64, SII ≤683.16, PNI >49.23, tumor distance from the anal margin >5cm, tumor length ≤5cm, tumor invasion of the bowel wall ratio ≤50%, lower T stage and N stage, good tumor regression response, absence of KRAS gene mutation, and mismatch repair protein deficiency. And multivariate analysis showed that age (HR=0.385, P=0.007), NLR (HR=0.294, P=0.011), cT stage (HR=0.287, P<0.001), and tumor regression grade (HR=0.273, P<0.001) were significant factors influencing DFS in patients receiving neoadjuvant chemoradiotherapy. For OS, age (HR=0.497, P=0.035), cT stage (HR=0.387, P=0.001), and tumor regression grade (HR=0.307, P<0.001) were significant factors influencing OS in patients receiving neoadjuvant chemoradiotherapy.ConclusionAge, cT stage, NLR, and tumor regression grade are significant factors influencing DFS and OS in patients with locally advanced rectal cancer. Younger age, lower cT stage, lower NLR value, and lower tumor regression grade are associated with better survival prognosis.